Youth drinking cultures in a digital world: alcohol, social media and cultures of intoxication - Lyons, Antonia C.; McCreanor, Tim; Goodwin, Ian; Barnes, Helen Moewaka (Routledge studies in public health, 2017)
Introduction to youth drinking cultures in a digital world / Antonia C. Lyons, Timothy McCreanor, Ian Goodwin & Helen Moewaka Barnes -- Neoliberalism, alcohol, and identity : a symptomatic reading of young people's drinking cultures in a digital world / Ian Goodwin & Christine Griffin -- Social locations : class, gender and young people's alcohol consumption in a digital world / Lin Bailey & Christine Griffin -- Curating identity : drinking, young women, femininities and social media practices / Jo Lindsay & Sian Supski -- Masculinities, alcohol consumption and social networking / Antonia C. Lyons & Brendan Gough -- Ethnicity/culture, alcohol and social media / Helen Moewaka Barnes, Patricia Niland, Lina Samu, Acushla Dee Sciascia & Timothy McCreanor -- Understanding social media as commercial platforms for engaging with young adults / Nina Michealidou -- Alcohol corporations and marketing in social media / Nicolas Carah -- Mobile technologies and spatially structured real-time marketing / Rebeca Monk & Derek Heim -- Creating powerful brands / Richard Purves -- Social media affordances for curbing alcohol consumption : insights from Hello Sunday Morning blog posts / Hélène Cherrier, Nicholas Carah & Carla Meurk -- Regulating social media : reasons not to ask the audience / Andy Ruddock -- Restricting alcohol marketing on social media in Finland / Marjatta Montonen & Ismo Tuoninen -- New marketing, new policy? Emerging debates over regulating alcohol campaigns in social media / Sarah Mart -- Digital alcohol marketing and the public good : industry, research and ethics / Tim McCreanor, Helen Moewaka Barnes, Antonia C. Lyons & Ian Goodwin